All about six sigma : - Brussee, Warren (McGraw-Hill, 2006)
All About Six Sigma provides clear, straightforward explanations of how to apply Six Sigma so no matter what your experience, you can introduce, implement, and complete a Six Sigma project. Warren Brussee presents a simplified form of the most common Six Sigma tools, providing techniques for easy application while optimizing processes and results.